"Steeped in Oil": The Socio-Psychological Factors and Processes That Influence Community Members' Attitudes toward Economic Diversification in an Oil and Gas-Producing Community. Issue 9 (2nd September 2022) - Murphy, Kathleen; Stone, Kathryn; Cameron, Emma Stirling; Strand, Lola; Combs, Chaise; Khan, Anam; Ungar, Michael
Abstract: Oil and gas-producing communities are threatened by a precarious oil market and global commitments to transition to a greener economy. Economic diversification has been proposed as a potential strategy for supporting the resilience of these communities amidst such challenges. We sought to explore community members' attitudes toward the future of their small oil and gas-producing Canadian community to understand the socio-psychological factors and processes that influence their support for economic diversification and those which reinforce path dependency. This qualitative study involved interviews with 37 adults in the community, and a subset of 16 of those participants engaged in transect walks to further explore emerging themes. While the recent prolonged economic downturn prompted some participants' willingness to diversify, the deeply ingrained culture and identity as an oil and gas town, the 'golden handcuffs' of the industry, and optimism for another boom, acted to reinforce path dependency.